2022
DOI: 10.3390/en15144938
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Pore-Scale Visualization and an Ultrasonic Test System of Methane Hydrate-Bearing Sediments

Abstract: The acoustic characteristics of hydrates are important parameters in geophysical hydrate exploration and hydrate resource estimation. The microscale distribution of hydrate has an important influence on the acoustic response of a hydrate-bearing reservoir. Although microscale hydrate distributions can be determined using means such as X-ray computed tomography (X-CT), it is difficult to obtain acoustic parameters for the same sample. In this study, we developed an experimental system that integrated pore-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Compression wave velocity of the specimen is monitored by using a pair of acoustic transducers connected to an HS-CS4EL acoustic tester (Xiangtan Tianhong Electronics Research Institute, Xiangtan, China), and the penetration depth of each acoustic transducer is 1 mm. This seismic wave monitoring system has been used in previous studies to measure the wave velocity of hydrate-bearing sands [43,44].…”
Section: Experimental Apparatus and Materialsmentioning
confidence: 99%
“…Compression wave velocity of the specimen is monitored by using a pair of acoustic transducers connected to an HS-CS4EL acoustic tester (Xiangtan Tianhong Electronics Research Institute, Xiangtan, China), and the penetration depth of each acoustic transducer is 1 mm. This seismic wave monitoring system has been used in previous studies to measure the wave velocity of hydrate-bearing sands [43,44].…”
Section: Experimental Apparatus and Materialsmentioning
confidence: 99%
“…Several laboratories have developed devices for simultaneous visual observations and geophysical measurements. For example, the Qingdao Institute of Marine Geology, China Geological Survey, has developed a joint X-CT and acoustic/electrical detection device. Bu et al conducted a joint X-CT and P-wave velocity/resistivity test. They found that the sample’s P-wave velocity did not increase linearly with the increase of hydrate saturation but presented stage characteristics related to the change of the hydrate morphology.…”
Section: Joint Detectionmentioning
confidence: 99%
“…Variation in hydrate morphology of CT images and P-wave velocity (a) or resistivity (b) characteristics of hydrate-bearing sand with hydrate saturation (S h ). (a) Adapted from open access ref . (b) Adapted with permission from.…”
Section: Joint Detectionmentioning
confidence: 99%